Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai di Museum Siginjai Kota Jambi - Mardani Hasnur (Universitas Batanghari Jambi, 2021)
Organization and employees are two things that need each other. Improving employee performance will bring progress for the institution or organization to be able to continue to carry out the goals to be achieved. Leadership style is a process of directing, influencing, and motivating members to achieve organizational goals to help create a more productive work atmosphere at work. The leader's behavior affects the understanding, psychological condition, and performance of members. The Siginjei Museum in Jambi City is one of the is a management implementing unit which is a parliamentary institution that serves the interests of the community and its progress does not seek profit but seeks to collect, maintain, research, exhibit, and communicate material objects of humans and the environment for the purposes of study, education, and enjoyment. This study aims to describe and analyze the leadership and performance of employees at the Siginjei Museum, Jambi City. Research data obtained from respondents through questionnaires, focus groups, and panels, or also data from interviews with informants. The analytical method used is descriptive analysis, verification, and simple regression analysis. Statistical analysis was carried out using the SPSS 20 program. Based on the results of interviews and questionnaires, it shows that the leadership style and performance of employees at the Siginjei Museum in Jambi City are good. The regression model obtained is: Y= 25,265 + 0,535 X+ e. If the leadership style increases by 1 point or temporary unit, then the employee performance variable will increase by 0,535. Based on the t-test shows that leadership style has a positive and significant effect on employee performance because the significance value is 0,001 < 0,05. So it can be said based on the results of hypothesis testing that leadership style affects employee performance by 24.3% and the rest is influenced by other variables.